Makna Tradisi Ruwatan Petirtaan Candi Jolotundo Sebagai Sarana Pelestarian Air - Yosi Maurin; Neni Wahyuningtyas; I Nyoman Ruja (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2020)
Culture is a Indonesia’s treasure. One form of culture is tradition. One Example which belongs to tradition and still exist nowahdays is Ruwatantradition in Petirtaan Jolotundo Temple. The purpose of this study is to describe the history, the process, and the meaning of ruwatantradition. This study uses qualitative research within descriptive approach. The study was located at Petirtaan Jolotundo Temple, precisely on the Slope of Penanggungan Mountain. There are two froms of data,primary and secondary data. Observation, interviews, and documentationis used as data collection techniques. Based on the research can be concluded that ruwatantradition has existed since long ago which is known as a barikansumber. The existence of this tradition is a gratitude for the abundant water resources that can be utilized. Since 2007-2008, this tradition began to be packaged and enlivened so that an annual event was organized, including sumaninggah, grand carnival, release of birds and tree planting, and manunggaling tirta. Ruwatantraditionmeans a reminder of the beginning to the end of life aimed at humans and the environment.The meaning of ruwatanis depends on the trust of each individual, trust is divided into sacred and profane.